THE INFLUENCE OF “HALAL TOURISM STANDARDS” IN RELIGIOUS TOURISM DEVELOPMENT IN UZBEKISTAN - Djurayeva Nafisa Bakhodirovna (Journal of new century innovations, 2023)
Abstract. Halal Tourism is one indicator of success in bringing in foreign exchange, especially in the tourism sector. In addition, halal tourism can provide security and comfort for Muslim tourists visiting the country. This study aims to find out the potential of the halal tourism industry in Uzbekistan, a country located in Central Asia, while developing halal tourism. This articles discusses Halal tourism standards in religious tourism in case of Uzbekistan.